PENGEMBANGAN MODUL PEMBELAJARAN SOSIOLOGI BERBASIS ISLAM PADA MADRASAH ALIYAH NEGERI DI PROVINSI RIAU - Bambang Kariyawan; M Nazir; Abu Anwar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This paper aims to determine the integration model in the development of Islamic-based Sociology modules and their implementation at Islamic Senior High Schools in Riau Province. The research method used is research and development (Research and Development) with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The schools that were sampled in the research and module trials consisted of 8 Islamic Senior High Schools located in Riau Province. With data collection techniques in the form of questionnaires, interviews, and observations, the results obtained that the integration model in the development of an Islamic-based Sociology module can be displayed in the aspect of content feasibility with indicators such as the suitability of the material with the SK and KD, the accuracy of the material, the up-to-date of the material, and encouraging curiosity was assessed 64% very good. The aspect of presentation feasibility with indicators of presentation technique, presentation support, learning presentation, and coherence in the flow of thought is considered very good 51%. Aspects of contextual assessment with indicators of contextual nature and contextual components rated 71% very good. From the linguistic aspect, it was rated 69% very well and the graphic aspect was rated at 54% as very good. Based on interviews and observations of testing the use of the module on students, 72% of the Sociology module based on Islam is very feasible to use. Suggestions and views from sociologists, commentators on the Qur'an and hadith, and module preparation experts add to the completeness and accuracy of the material and appearance of this module. The Islamic-based Sociology module can be developed at other levels and general subjects in the Islamic Senior High School environment. Keywords: Integration, Module, Sociology, Islam, Islamic Senior High SchoolAbstrakTulisan ini bertujuan untuk mengetahui model integrasi dalam pengembangan modul Sosiologi berbasis Islam beserta implementasinya pada Madrasah Aliyah Negeri di Provinsi Riau. Metode penelitian yang digunakan adalah penelitian dan pengembangan (Research and Development) dengan model ADDIE (Analiyze, Design, Development, Implementation, and Evaluation). Madrasah yang dijadikan sampel dalam penelitian dan uji coba modul terdiri dari 8 Madrasah Aliyah Negeri yang berada di Provinsi Riau. Dengan teknik pengumpulan data berupa angket, wawancara, dan observasi diperoleh hasil bahwa model integrasi dalam pengembangan modul Sosiologi berbasis Islam dapat ditampilkan dalam aspek kelayakan isi dengan indikator berupa kesesuaian materi dengan SK dan KD, keakuratan materi, kemutakhiran materi, dan mendorong keingintahuan dinilai 64% sangat baik. Aspek kelayakan penyajian dengan indikator teknik penyajian, pendukung penyajian, penyajian pembelajaran, koherensi dan keruntutan alur pikir dinilai 51% sangat baik. Aspek penilaian kontekstual dengan indikator hakikat kontekstual dan komponen kontekstual dinilai 71% sangat baik. Dari aspek kebahasaan dinilai 69% sangat baik dan aspek kegrafikaan dinilai 54% sangat baik. Berdasarkan wawancara dan observasi ujicoba penggunaan modul pada siswa bahwa 72% modul Sosiologi berbasis Islam ini sangat layak untuk digunakan. Saran dan pandangan dari ahli Sosiologi, ahli tafsir Al Quran dan hadis, dan ahli penyusunan modul menambah lengkap dan ketepatan materi serta penampilan modul ini. Modul Sosiologi berbasis Islam dapat dikembangkan pada jenjang dan mata pelajaran umum yang lain di lingkungan Madrasah Aliyah. Kata Kunci: Integrasi, Modul, Sosiologi, Islam, MAN.